PROBLEMS REGARDING CLT IMPLEMENTATION AT HIGHER SECONDARY LEVEL: A CASE STUDY IN BOTH URBAN AND RURAL AREAS IN BANGLADESH. - Islam, Musfikul (LLT Journal: A Journal on Language and Language Teaching, 2021)
This article tries to find out the explanations behind the implementation of CLT approach in the higher secondary level and attempts to produce a real data of CLT implementation in both rural and urban areas in Bangladesh. It also looks at the factors that make this teaching approach difficult to implement. This study examined both teachers’ and students’ perceptions, opinions, and perspectives of the English language at the higher secondary level. To achieve the objectives of the study, a mixed-method approach has been undertaken to conduct the methodology of the study where a range of methods such as Questionnaire, Interview and Classroom Observation Checklist have been used. The outcomes reveal various types of obstacles which are: a huge number of students in CLT classroom, small size of classroom, insufficiency of modern materials. It also disclosed that maximum students are not able to understand the English lecture in the classroom, teachers are not trained to maintain the classroom by following CLT method and some of the trained teachers are refused to apply CLT approach as well. Based on the findings, this study tries to propose some processes for reversing the current situation that is happening at present within the educational system in Bangladesh.